Fuzzy Logic dalam Pengontrolan Nilai Intensitas Cahaya LED pada Mini Plant Factory Budidaya Tanaman Pak Choy (Brassica Chinensis L.) Hidroponik - Choirul Umam; Fahmi Arief Rahman; Mohammad Syafii; Nurul Hidayat (Rekayasa, 2023)
Ideally, the Pak Choy plant (Brassica Chinensis L) is cultivated with microenvironmental conditions of temperature 150C- 320C, humidity 60% - 80% and the same intensity of sunlight as other vegetable plants, namely in a vegetative vase of 300-400 micromols/m2/second and a period of generative 500-1000 micromols/m2/sec . The challenge of agriculture today is to meet the increasing need for food with limited land and uncertain plant microenvironmental conditions, one solution to this problem is planting using a plant factory system. Fuzzy logic has an effective method for controlling plant factory control systems, due to its flexibility and simple calculations. The purpose of this research is to find the PWM value in the plant factory control system that suits the optimal needs of pak choy vegetable cultivation. There are 4 stages in the research, namely the primary data input of the LED plant factory, Fuzzyfication, Fuzzy Interface System and Defuzzification. Data was taken using a lux meter and there were a total of 56 fuzzy rules and 4 fuzzy rules that did not have a value of 0. The lighting level/light intensity control system based on fuzzy logic was obtained with a PWM (Pulse Width Modulation) value of 872.1662 for a light intensity set point of 8000 Lux.